CUSTOMER SATISFACTION DETERMINANTS IN NIGERIA TELECOMMUNICATION FIRMS: THE CASE OF CUSTOMER SUPPORT SERVICES AND ASSURANCE - ADIELE, KENNETH C.; GREND., MIEBAKA, D. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This study examines the effect of customer support services and service assurance on customer satisfaction. The study population was the five functional telecommunication companies registered and listed by the Nigeria Communication Commission (NCC) and the Corporate Affairs Commission (CAC). Data was generated from 200 customers of these mobile service providers which were randomly chosen. Out of the 200 distributed copies of structured questionnaire, 173 copies were returned and qualified for use. Descriptively, the study variables were presented and inferentially, the simple linear regression analysis was used in testing the various hypotheses. It was found that a significant relationship exist between customer support services, service assurance and customer satisfaction. The study therefore concluded that customer support services and service assurance affect customer satisfaction. Hence, the authors recommended that in order for the telecom service providers to enhance their level of customer satisfaction they should improve their service assurance while taking cognizance of customer support services since it significantly impacts on their level of customer satisfaction.